2004
DOI: 10.3366/afr.2004.74.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Children's Children: Time and Relatedness in Eastern Uganda

Abstract: This article brings two analytic perspectives to bear on temporal aspects of relations to children's children. The first, which we call processual time, is the long-term, ‘experience-distant’, view of household developmental cycles over a historical period. Beginning with this approach, we describe the arrangements of family and marriage that provide the framework for people's relations to the children of their sons and of their daughters in Bunyole County, eastern Uganda. Household survey material collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 1 publication
2
20
0
2
Order By: Relevance
“…The lens of relatedness requires us to consider which of the possible (female) relatives are closest to the children and why. Grandparents have a special position in the lives of children in many communities in Uganda, and there is often more informal intimacy with grandparents than with parents (Baarøy, 1999;Whyte & Whyte, 2004). Many of the children in this study indicated that they had a loving relationship with grandparents, especially with grandmothers, and they listed the actions that showed how their grandmothers cared.…”
Section: Gender and Practices Of Relatednessmentioning
confidence: 86%
See 1 more Smart Citation
“…The lens of relatedness requires us to consider which of the possible (female) relatives are closest to the children and why. Grandparents have a special position in the lives of children in many communities in Uganda, and there is often more informal intimacy with grandparents than with parents (Baarøy, 1999;Whyte & Whyte, 2004). Many of the children in this study indicated that they had a loving relationship with grandparents, especially with grandmothers, and they listed the actions that showed how their grandmothers cared.…”
Section: Gender and Practices Of Relatednessmentioning
confidence: 86%
“…Although there are differences between countries with regards to who within the family assumes the primary responsibility for the care of children (Gillespie et al, 2005), there is general agreement that kinship obligation is the most important factor (Nyambedha et al, 2003a;Madhavan, 2004;Whyte & Whyte, 2004;Howard et al, 2006). Kinship and family networks become even more important during sickness (Xu et al, 2010;Kyaddondo et al, 2013).…”
Section: The Kinship Obligation and Idealmentioning
confidence: 99%
“…However, it can’t be denied that cultural and historical circumstances influence the perception and meaning of time and future. According to a study in Eastern Uganda, the historical linear passage of time is often reframed in rural areas as time related to other people, linking the ancestors to future children (Whyte and Whyte, 2004). While it seems reasonable to assume that the concept of future expectations as a linear concept of time is applicable in a rural Ugandan setting, any instrument measuring future expectations should take this intersubjectivity into account by asking about future family plans and relations to family members.…”
Section: Methodsmentioning
confidence: 99%
“…The tasks and skills in Table 1 (highlighted in italics) are the main areas where we might expect children or relationships with children to play a role in PLWH self-management, based on both existing evidence and broader knowledge about inter-generational relationships and the expected roles of children in the Ugandan context (Rutakumwa, Zalwango, Richards, & Seeley, 2015;Whyte & Whyte, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%